Gross motor coordination in relation to weight status: a longitudinal study in children and pre-adolescents - Biino, Valentina; Pellegrini, Barbara; Zoppirolli, Chiara; Lanza, Massimo; Gilli, Federica; Giuriato, Matteo; Schena, Federico (Frontiers in Public Health, 2023)
Gross Motor Coordination (GMC) is crucial for adequate developments of motor competence. Our purpose in this semi-longitudinal study was to evaluate the influence of BMI on GMC in children and pre-adolescents of both sexes, across years. We evaluated 117 subjects (aged 8 -13) belonging to 3 different cohorts for four consecutive years, providing data over six years (classes). GMC was assessed through the Körperkoordinationstest für Kinder (KTK) test. Class and weight-status effects were then evaluated dividing the subjects into normal-and over-weight group, based on the weight status. Significant increase across classes was found for BMI (p<.001) and KTK Raw Score (p<.001) and a decrease for KTK normalized score (MQ) (p=.043). Significantly lower MQ values were found for girls. Absolute GMC increased across years and was not different between boys and girls.Correlations between GMC scores and BMI were negative and significant in 5 upon 6 classes. It was confirmed that over-weight subjects have a lower MQ and RAW values than normal-weight subjects, with no class by weight status interaction. The level of competence and its development are strictly dependent on weight status during childhood and pre-adolescence. The present investigation suggests that an adequate development of GMC needs not only targeted physical education programs but also the promotion of healthy habits, aiming at maintaining a normal-weight status during childhood and pre-adolescence.